Intergenerational Transmission of Effects of Women's Stressors During Pregnancy: Child Psychopathology and the Protective Role of Parenting - Ahmad, Shaikh I.; Shih, Emily W.; LeWinn, Kaja Z.; Rivera, Luisa; Graff, J. Carolyn; Mason, W. Alex; Karr, Catherine J.; Sathyanarayana, Sheela; Tylavsky, Frances A.; Bush, Nicole R. (Frontiers in Psychiatry, 2022)
Objective: Experiences of stress and adversity, such as intimate partner violence, confer risk for psychiatric problems across the life span. The effects of these risks are disproportionately borne by women and their offspring – particularly those from communities of color. The prenatal period is an especially vulnerable period of fetal development, during which time women’s experiences of stress can have long-lasting implications for offspring mental health. Importantly, there is a lack of focus on women’s capacity for resilience and potential postnatal protective factors that might mitigate these intergenerational risks and inform intervention efforts. The present study examined intergenerational associations between women’s prenatal stressors and child executive functioning and externalizing problems, testing maternal parenting quality and child sex as moderators, using a large, prospective, sociodemographically diverse cohort. Methods: We used data from 1034 mother-child dyads (64% Black, 30% White) from the Conditions Affecting Neurocognitive Development and Learning and Early Childhood (CANDLE) pregnancy cohort within the ECHO PATHWAYS consortium. Women’s prenatal stressors included stressful life events (pSLE) and intimate partner violence (pIPV). Measures of child psychopathology at age 4-6 included executive functioning and externalizing problems. Parenting behaviors were assessed by trained observers, averaged across 2 sessions of mother-child interactions. Linear regression models were used to estimate associations between women’s prenatal stressors and child psychopathology, adjusting for confounders and assessing moderation effects by maternal parenting quality and child sex. Results: Women’s exposures to pSLE and pIPV were independently associated with child executive functioning problems and externalizing problems in fully-adjusted models. Maternal parenting quality moderated associations between pSLE and both outcomes, such that higher parenting quality was protective for the associations between women’s pSLE and child executive functioning and externalizing problems. No moderation by child sex was found. Discussion: Findings from this large, sociodemographically diverse cohort suggest women’s exposures to interpersonal violence and major stressful events – common for women during pregnancy – may prenatally program her child’s executive functioning and externalizing problems. Women’s capacity to provide high quality parenting can buffer this intergenerational risk. Implications for universal and targeted prevention and early intervention efforts to support women’s and children’s wellbeing are discussed.